1998
DOI: 10.1161/01.str.29.5.1063
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Carotid Artery Vasospasms Causing Cerebral Ischemia

Abstract: Background-The etiology of cerebral ischemic accidents in young adults often remains unclarified. Case Description-A 32-year-old woman presented after multiple episodes of left monocular visual impairment and right-sided focal signs. MRI revealed a low-flow infarction on the left; color-coded duplex sonography (CCDS), however, showed normal vascular findings. During the inpatient rehabilitation, a renewed visual impairment occurred; an immediate CCDS examination now demonstrated a filiform stenosis of the left… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
1
2

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 10 publications
1
12
1
2
Order By: Relevance
“…In contrast to other case reports [6, 7, 12] which reported positive effects of calcium channel inhibitors and corticoids, this treatment was not effective in our patient. In addition, neither oral anticoagulation nor platelet inhibitors prevented new stroke episodes in our case.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast to other case reports [6, 7, 12] which reported positive effects of calcium channel inhibitors and corticoids, this treatment was not effective in our patient. In addition, neither oral anticoagulation nor platelet inhibitors prevented new stroke episodes in our case.…”
Section: Discussioncontrasting
confidence: 99%
“…Evidence is accumulating that recurrent vasospasms of the extracranial ICA are a rare but important cause of ischemic disorders mainly in young patients [6, 7, 8, 9, 10, 11, 12, 13, 14]. While previous cases have been associated with migraine [5, 10], we describe a patient with recurrent non-migrainous vasospasms of the extracranial ICA.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Furthermore, transesophageal echocardiography was obtained in only 18.2% patients, so that some cardiac or aortic arch lesions may have been missed. Also, our protocol did not include serial retinal imaging or transcranial Doppler testing to identify patients with vasospastic amaurosis fugax [17]. The true prevalence of each of these etiologies remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…To date, several studies have reported transient and recurring stenosis of the extracranial internal carotid artery (ICA) [ Table 1 ]. [ 1 3 4 5 6 7 9 10 11 13 14 ] These cases usually showed completely resolved stenosis, to smooth and normal arterial walls, within hours to days, but had multiple recurrences. Thus, vasospasm has been presumed as the cause of the stenosis.…”
Section: Introductionmentioning
confidence: 99%